Preparedness and Adaptive Capacity of Students for Landslide Disasters in Karangkobar, Central Java, Indonesia - Safriani, Eka Wulan; Wibowo, Yunus Aris (KnE Social Sciences, 2022)
Landslides are disasters that often hit several areas in Banjarnegara Regency. The worst landslide incident which claimed many victims occurred on December 12, 2014, in Jemblung Hamlet, Sampang Village, Karangkobar District, which resulted in the settlement of one hamlet being buried. The high risk of landslides in the Karangkobar District necessitates adequate preparedness and capacity. The focus of the research was to determine (1) the level of student preparedness for landslides in Karangkobar District, (2) the level of student adaptive capacity for landslides in Karangkobar District, and (3) the relationship between preparedness and student adaptive capacity. The researchers used a quantitative descriptive method and collected data using questionnaires, observations, and secondary data on disaster events from the Central Regional Management Agency (BPBD) of Banjarnegara Regency. Four junior high schools in the Karangkobar District were studied. The findings showed that preparedness was homogeneous across the four schools. The level of preparedness was moderate, with an index of 71% - 75%. MTs Muhammadiyah Karangkobar was in the high category for adaptive capacity with 80.54%, and other schools were classified as medium. Preparedness correlated with adaptive capacity, with a significance value of 0.035 (<0.05). Keywords: disaster, preparedness, adaptive capacity, landslide